2005
DOI: 10.1371/journal.pgen.0020010.eor
|View full text |Cite
|
Sign up to set email alerts
|

Pol II-expressed shRNA knocks down Sod2 gene expression and causes phenotypes of the gene knockout in mice

Abstract: RNA interference (RNAi) has been used increasingly for reverse genetics in invertebrates and mammalian cells, and has the potential to become an alternative to gene knockout technology in mammals. Thus far, only RNA polymerase III (Pol III)-expressed short hairpin RNA (shRNA) has been used to make shRNA-expressing transgenic mice. However, widespread knockdown and induction of phenotypes of gene knockout in postnatal mice have not been demonstrated. Previous studies have shown that Pol II synthesizes micro RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“…Severe reduction of SOD2 expression in mice and flies causes a number of phenotypes including short life span, neuronal loss, and mitochondrial dysfunction (Li et al, 1995;Lebovitz et al, 1996;Kirby et al, 2002;Duttaroy et al, 2003;Xia et al, 2006). Here, we used Drosophila to investigate the role of this enzyme in demographic mortality parameters, nervous system pathology and behavioral senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Severe reduction of SOD2 expression in mice and flies causes a number of phenotypes including short life span, neuronal loss, and mitochondrial dysfunction (Li et al, 1995;Lebovitz et al, 1996;Kirby et al, 2002;Duttaroy et al, 2003;Xia et al, 2006). Here, we used Drosophila to investigate the role of this enzyme in demographic mortality parameters, nervous system pathology and behavioral senescence.…”
Section: Discussionmentioning
confidence: 99%
“…1B and 1C) at the same site in the loop region had almost no effect on mature let-7 production, indicating that the loop sequence specificity is important for pri/pre-miRNA processing. Recently, a human miR-30-based shRNA design showed promising efficiency in gene knockdown in several cell culture and mammal systems (Silva et al, 2005;Xia et al, 2006). Our observations strongly suggested that the efficiency and specificity of miRNAbased shRNAs could be further improved by optimizing the primiR-30 loop sequence.…”
Section: Discussionmentioning
confidence: 75%
“…3 ). Intron cloned HcRed1 construct was successfully utilized to generate transgenic miRNA-expressing cell lines and animals [4][5] and geneknockout mice for human disease research 6 . The authors show successful splicing of pre-mRNA and further excision into small miRNA, which in turn are able to trigger targeted gene silencing making this type of construct a good platform for miRNA expression 3 .…”
Section: Introductionmentioning
confidence: 99%